Unveiling the potential applications of buds of Lonicera japonica Thunb. var. chinensis (Wats.) Bak based on in vitro biological activities, bio-active components, and potential applications coupled to targeted metabolomics - Liu, Zhenying; Cheng, Yunxia; Xiang, Yaoting; Chao, Zhimao (Frontiers in Plant Science, 2024)
Introduction The buds of Lonicera japonica Thunb. var. chinensis (Wats.) Bak, commonly named red honeysuckle, have attracted attention because of their bright colors. However, owing to the lack of systematic studies, the potential applications of red honeysuckle are not clear, and its development and utilization have not been well known. Methods In this study, compared with the buds of L. japonica Thunb. (honeysuckle), the potential applications of red honeysuckle were explored based on biological activities, bio-active components, and sensory flavor combined with widely targeted metabolomics. Results As a result, in vitro tests showed that it had a stronger antioxidant and a stronger inhibitory effect on the growth of Escherichia coli and Staphylococcus aureus. There was no cytotoxicity on LPS-induced RAW264.7 cells in its aqueous extract using the CCK-8 method. Moreover, it also had a stronger effect on inhibiting the expression of inflammatory factors such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β). The content of its bio-active components chlorogenic acid and cynaroside was significantly higher (p ≤ 0.001) than that of green honeysuckle. Widely targeted metabolomics analysis revealed that 4 volatile metabolites, such as (E)-4-hexene-1-ol and pyrazole, and 21 non-volatile metabolites, such as macranthoside B and oleanolic acid-3-O-glc(1-2)-(ara)-28-O-glucoside ester, were specific in red honeysuckle. Interestingly, 14 specific terpenoid metabolites were triterpenoid saponins, indicating a stronger biological activity in red honeysuckle. The sensory flavor analysis showed that the red honeysuckle had a stronger herbal and lighter floral flavor. Discussion In conclusion, red honeysuckle had great development value with potential applications in medicines, foods, beverages, pigment additives, and health products.